2021
DOI: 10.1186/s12870-021-03191-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of bZIP transcription factors and their expression profile under abiotic stresses in Chinese pear (Pyrus bretschneideri)

Abstract: Background In plants, basic leucine zipper transcription factors (TFs) play important roles in multiple biological processes such as anthesis, fruit growth & development and stress responses. However, systematic investigation and characterization of bZIP-TFs remain unclear in Chinese white pear. Chinese white pear is a fruit crop that has important nutritional and medicinal values. Results In this study, 62 bZIP genes were comprehensively ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 96 publications
(108 reference statements)
1
13
0
Order By: Relevance
“…In the organization of exons/introns, a high degree of conservation has been observed, which is consistent with the high degree of similarity found by multiple alignments between protein sequences, which gives high similarities between them. The evolutionary analysis suggested that structural gene diversity is the primary source for the evolution of multigene families ( Xu et al, 2012 ; Manzoor et al, 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…In the organization of exons/introns, a high degree of conservation has been observed, which is consistent with the high degree of similarity found by multiple alignments between protein sequences, which gives high similarities between them. The evolutionary analysis suggested that structural gene diversity is the primary source for the evolution of multigene families ( Xu et al, 2012 ; Manzoor et al, 2021b ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the banana WRKY family is involved in ABA-induced cold tolerance by directly activating NCED expression to increase ABA levels [49]. The ERF family is involved in regulating tomato ripening by acting on ethylene biosynthesis [50], and bZIP may be involved in ripening senescence in pears by participating in the regulation of the biosynthetic pathways of ABA and MeJA [51]. These transcription factors affect plant growth and development overall by regulating hormone synthesis, sugar synthesis, and other pathways.…”
Section: Discussionmentioning
confidence: 99%
“…All GAox gene chromosomal positions were retrieved from a genome database (see text footnote 1), and Mapinspect software 11 was used for the visualization of these positions ( Manzoor et al, 2021b , c ). Moreover, the Conserved Domain Architecture Retrieval Tool (CDART), HMMER program 12 , and protein family database (Pfam) 13 were utilized for obtaining the conserved domain of GAox protein of P. avium , Fragaria vesca , and P. mume ( Johnson et al, 2010 ; Mistry et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%